DEVELOPING COMMUNICATIVE COMPETENCE THROUGH TASK-BASED LANGUAGE TEACHING IN EFL CLASSROOMS (International Conference on Education and Innovation, 2025)
This thesis explores the effectiveness of Task-Based Language Teaching (TBLT) as a methodology for developing communicative competence among learners of English as a Foreign Language (EFL). The research investigates theoretical foundations, practical classroom implementations, and outcomes related to language fluency, accuracy, and learner autonomy. Findings demonstrate that TBLT significantly enhances communicative performance and learner engagement when aligned with meaningful real-world tasks.